The effect of music during warm up on anaerobic performance among players of DRB HICOM FC 2 / Muhammad Amiruddin Mohd Azman - Mohd Azman, Muhammad Amiruddin (2017)
Music been used generally as a powerful tools to enhance athlete's performance based on psychological variables. However, there are some issues about music effect on anaerobic performance in performance enhancement. The objective of this study is to investigate the effect of fast tempo music during warm up and short-term maximal performance on football players. This study involves of 24 players form ORB Hicom FC 2 from Kuala Lumpur Division I League. They needs to do both of the test which is with and without music. Heart rate before and after warm up, RPE, peak power, mean power and fatigue index were measured. Mixed factorial ANOV A was used to investigate the effect of music on heart rate, while independent t-test were used on RPE, peak power, mean power and fatigue index. Results indicates some significant interaction of music to variables listed, p<0.05 across the experimental session. In conclusion, there is a significant effect of music on heart rate and fatigue index on warm up and short-term maximal of football players.